Periostin staining within renal tissues from IgA nephropathy patients - Peepattra Wantanasiri; Bancha Satirapoj; Mongkon Charoenpitakchai; Pornanong Aramwit (Songklanakarin Journal of Science and Technology (SJST), 2018)
Periostin is a novel biomarker related to kidney disease progression. The aim of this study was to examine the level of periostin staining within renal tissue from IgA nephropathy patients. Immunohistochemistry for periostin was performed. The score of periostin staining and the correlation of periostin staining score with each pathological feature were evaluated. Positive periostin staining was found in renal tissue from IgA nephropathy patients including glomerular, interstitial, vascular and tubular areas. Tubular epithelial cell staining, tubular cell cast staining and periglomerular staining were common histologic features positive for periostin. Periglomerular staining were correlated with interstitial fibrosis as well as with tubular epithelial cell staining. In addition, tubular cell cast staining were correlated with tubular epithelial cell staining as well as with tubular atrophy staining. We concluded that periostin may be a promising biomarker in IgA nephropathy patients.